The potency of blumeatin and luteolin as caspase-1 inhibitor by molecular docking - Pratama, I Putu Ari Anggara Catur; Putra, I Made Harimbawa; Pujasari, Luh Wayan Sita; Dewi, Komang Dian Merta Sari; Laksmiani, Ni Putu Linda (Indonesian Young Scientist Group and UPN Veteran Jakarta, 2022)
COVID-19 infection induces inflammation by increasing cytokines such as IL-1b, IL-6, IL-18, IFN-γ, and TNF-α. IL-1b is generated by the involvement of caspase-1. Therefore, caspase-1 inhibitor can be potential for inflammation therapy caused by COVID-19 infection. This study aims to determine the potential of blumeatin and luteolin as anti-inflammatory agents by inhibiting caspase-1 using a molecular docking approach. This study was carried out by caspase-1 (PDB ID: 1RWK) preparation, blumeatin and luteolin structure optimization, docking protocol validation, and docking of blumeatin and luteolin on caspase-1. Bluematin and luteolin had a binding affinity of -5,63 kcal/mol and -5,93 kcal/mol, lower than Q158 native ligand (-3.92 kcal/mol). Similar amino acid residues in hydrogen bonds interaction were observed between Q158 native ligand, blumeatin, and luteolin with caspase-1 (GLN 283 and ARG 179). Blumeatin and luteolin are potentially anti-inflammation agents through the inhibition of the caspase-1 in silico.